Hearing loss and intellectual outcome in children treated for embryonal brain tumors: Implications for young children treated with radiation sparing approaches. (4th September 2021) - Moxon‐Emre, Iska; Dahl, Christine; Ramaswamy, Vijay; Bartels, Ute; Tabori, Uri; Huang, Annie; Cushing, Sharon L.; Papaioannou, Vicky; Laperriere, Normand; Bouffet, Eric; Mabbott, Donald J.
Abstract: Purpose: We investigate the impact of severe sensorineural hearing loss (SNHL) and for the first time evaluate the effect of unilateral versus bilateral SNHL on intellectual outcome in a cohort of children with embryonal brain tumors treated with and without radiation. Methods: Data were from 94 childhood survivors of posterior fossa (PF) embryonal brain tumors who were treated with either: (1) chemotherapy alone ( n = 16, 7.11 [3.41] years, 11M/5F), (2) standard‐dose craniospinal irradiation (CSI) and/or large boost volumes ( n = 44, 13.05 [3.26] years, 29M/15F), or (3) reduced‐dose CSI with a boost restricted to the tumor bed ( n = 34, 11.07 [3.80] years, 19M/15F). We compared intellectual outcome between children who: (1) did and did not develop SNHL and (2) developed unilateral versus bilateral SNHL. A Chang grade of ≥2b that required the use of a hearing aid was considered severe SNHL. Comparisons were made overall and within each treatment group separately. Results: Patients who developed SNHL had lower full scale IQ ( p = 0.007), verbal comprehension ( p = 0.003), and working memory ( p = 0.02) than patients without SNHL. No differences were observed between patients who had unilateral versus bilateral SNHL (all p > 0.05). Patients treated with chemotherapy alone who developed SNHL had lower mean working memory ( p = 0.03 ) than patients who did not develop SNHL. Among patients treated with CSI, no IQ indices differed between those with and without SNHL (all p > 0.05). Conclusions: Children treated for embryonal brain tumors who develop severe SNHL have lower intellectual outcome than patients with preserved hearing: this association is especially profound in young children treated with radiation sparing approaches. We also demonstrate that intellectual outcome is similarly impaired in patients who develop unilateral versus bilateral SNHL. These findings suggest that early intervention to preserve hearing is critical.